Opportunities In Librarianship: Alternatives for the Ghanaian Graduate - Alemna, A.A. (Ghana Library Journal, 1989)
This paper seeks to explore the options available to the Library school graduates in Ghana, examine the constraints that militate against their full exploitation, and make suggestions towards the utilization of these alternative opportunities. The paper therefore attempts to show what else the graduate of the Library School can do with his or her certificate, in the light of job opportunities in the country.